Metformin Reduces Thyroid Cancer Risk in Taiwanese Patients with Type 2 Diabetes - Tseng, Chin-Hsiao (Public Library of Science, 2014)
BACKGROUND: Whether metformin may affect thyroid cancer risk has not been studied. This study investigated the association between metformin use and thyroid cancer risk in Taiwanese patients with type 2 diabetes mellitus. METHODS: The reimbursement databases of all diabetic patients from 1996 to 2009 were retrieved from the National Health Insurance. An entry date was set at 1 January 2006 and 1,414,723 patients with type 2 diabetes were followed for thyroid cancer incidence until the end of 2009. Incidences for ever-users, never-users and subgroups of metformin exposure using tertile cutoffs for cumulative duration of therapy and cumulative dose were calculated and adjusted hazard ratios were estimated by Cox regression. Additional sensitivity analyses were conducted. RESULTS: There were 795,321 ever-users and 619,402 never-users, with respective numbers of incident thyroid cancer of 683 (0.09%) and 1,614 (0.26%), and respective incidence of 24.09 and 87.33 per 100,000 person-years. The overall fully adjusted hazard ratio (95% confidence interval) was 0.683 (0.598–0.780), and all categories of the dose-response parameters showed significantly lower risk with P-trends <0.0001. The protective effect of metformin on thyroid cancer incidence was also supported by sensitivity analyses, disregarding age (<50 or ≥50 years) and sex; and was not affected by excluding users of insulin, sulfonylurea, and insulin and/or sulfonylurea respectively, by previous diagnosis of other cancers or by potential detection examinations that might lead to differential diagnosis of thyroid cancer. CONCLUSIONS: This study provides evidence for the first time that metformin use in patients with type 2 diabetes may reduce the risk of thyroid cancer.